2016
DOI: 10.1016/j.colsurfb.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-concentration rhamnolipid on transport of Pseudomonas aeruginosa ATCC 9027 in an ideal porous medium with hydrophilic or hydrophobic surfaces

Abstract: The success of effective bioaugmentation processes for remediation of soil and groundwater contamination requires effective transport of the injected microorganisms in the subsurface environment. In this study, the effect of low concentrations of monorhamnolipid biosurfactant solutions on transport of Pseudomonas aeruginosa in an ideal porous medium (glass beads) with hydrophilic or hydrophobic surfaces was investigated by conducting miscible-displacement experiments. Transport behavior was examined for both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
22
0
2
Order By: Relevance
“…The retention of the glucose‐grown cells is only slightly weaker than hexadecane‐grown cells (i.e., hydrophobic cells). This is in contrast to transport of the cells in the ideal porous medium of glass beads, in which retention of hydrophobic cells is strong (∼80%) but retention of hydrophilic cells is significantly weaker (∼20%) [ Zhong et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The retention of the glucose‐grown cells is only slightly weaker than hexadecane‐grown cells (i.e., hydrophobic cells). This is in contrast to transport of the cells in the ideal porous medium of glass beads, in which retention of hydrophobic cells is strong (∼80%) but retention of hydrophilic cells is significantly weaker (∼20%) [ Zhong et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Successful bioaugmentation depends on effective transport of injected microorganisms over considerable distances and adequate distribution of the injected microorganisms throughout the contaminated zone. This has been a focus of numerous studies on bioaugmentation [ Bai et al ., ; Chen et al ., ; Li and Logan , ; Liu et al ., ; Zhong et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful bioremediation (bioaugmentation in particular) depends on effective transport of injected bacteria over considerable distances and adequate distribution of the injected bacteria throughout the contaminated area (Liu, Zhong, et al, ). However, the soil has a great adsorption capacity and straining potential for bacterial cells, which may significantly reduce the concentration of suspended bacterial cells as they transport (Zhong, Liu, et al, ). Rhamnolipids have been widely used to modify surface properties of both bacterial cells and soil particles to weaken bacterial attachment and enhance transport of bacteria in soil.…”
Section: Remediation Of Organic Contaminationmentioning
confidence: 99%
“…Recently, the low concentration of rhamnolipid (lower than CMC) was also reported to facilitate bacterial transport in subsurface for bioaugmentation applications. For example, it was reported that low concentration of rhamnolipid significantly attenuated hydrophobic interactions between P. aeruginosa cells and glass beads, and hence reduced cell adsorption and enhanced cell transport (Zhong, Jiang, et al, ; Zhong, Liu, et al, ). The effect of low‐concentration mono‐rhamnolipid on transport of P. aeruginosa cells in natural porous media (silica sand and a sandy soil) with or without hexadecane as the nonaqueous phase liquid (NAPL) was further investigated in the study of Liu, Zhong, et al (), wherein it was observed that transport of cells in natural porous media was enhanced by rhamnolipid through decreasing bacterial CSH, and the relative enhancement in the presence of NAPL was greater than that in the absence of NAPL.…”
Section: Remediation Of Organic Contaminationmentioning
confidence: 99%